'Re-engage' pilot study protocol: a nurse-led eHealth intervention to re-engage, educate and empower childhood cancer survivors. Issue 4 (12th April 2018) - Signorelli, Christina; Wakefield, Claire E; Johnston, Karen A; Fardell, Joanna E; Brierley, Mary-Ellen E; Thornton-Benko, Elysia; Foreman, Tali; Webber, Kate; Wallace, W Hamish; Cohn, Richard J
Abstract : Introduction: Many childhood cancer survivors are disengaged from cancer-related follow-up care despite being at high risk of treatment-related late effects. Innovative models of long-term follow-up (LTFU) care to manage ongoing treatment-related complications are needed. 'Re-engage' is a nurse-led eHealth intervention designed to improve survivors' health-related self-efficacy, targeted at survivors disengaged from follow-up. Re-engage aims to overcome survivor- and parent-reported barriers to care and ensure survivors receive the care most appropriate to their risk level. Methods and analysis: This study will recruit 30 Australian childhood cancer survivors who are not receiving any cancer-related care. Participation involves two online/telephone consultations with a survivorship nurse for medical assessment, a case review, risk stratification and creation of a care plan by a multidisciplinary team of specialists. We will assess the feasibility of implementing 'Re-engage' and its acceptability to participants and health professionals involved. The primary outcome will be survivors' health-related self-efficacy, measured at baseline and 1 and 6 months postintervention. Secondary outcomes will include the effect of 'Re-engage' on survivors' health behaviours and beliefs, engagement in healthcare, information needs and emotional well-being. We will also document the cost per patient to deliver 'Re-engage'. If Re-engage is acceptable, feasible and demonstrates early efficacy, it may have the potential to empower survivors in coordinating their complex care, improving survivors' long-term engagement and satisfaction with care. Ideally, it will be implemented into clinical practice to recall survivors lost to follow-up and reduce the ongoing burden of treatment for childhood cancer. Ethics and dissemination: The study protocol has been approved by the South Eastern Sydney Local Health District Human Research Ethics Committee (reference number: 16/366). The results will be disseminated in peer-reviewed journals and at scientific conferences. A lay summary will be published on the Behavioural Sciences Unit website. Trial registration number: ACTRN12618000194268.